The Birchwood Cafe Cookbook : Good Real Food - Singleton, Tracy; Paulsen, Marshall, 1979- (Book collections on Project MUSE., 2015)
"Here is the Birchwood Cafe's lighthearted, innovative menu: hearty hand pies and multigrain salads, decadent pastries, and award-winning desserts. Organized by eight seasons, these dishes are inspired by the way weather affects our appetites and determines what comes from our land." from publisher's website.